(untitled) (Journal of Geography and Environmental Management, 2017)
The urgency of the safety of the components of the natural environment of Central Kazakhstan is due, firstly, to the long development of solid minerals and, in connection with this, the huge expenditure of energy and water resources, and secondly, to the use of obsolete mining technologies. It is established that the risk of industrial accidents decreases as technology and technology develop. The existing and emerging problems described and analyzed in this paper are not exhaustive. The subsoil, being the object and operational basis of mining, refers to the elements of the biosphere, the protection of which should provide for the provision of scientifically sound and economically justified completeness and complexity of use. In this regard, it seems advisable to develop and approve national standards and codes of practice in the field of land reclamation, as well as the procedure for production in mining enterprises, to fix the deadlines for the operation of enterprises, to establish specific ways of compensating damage caused to environmental objects, to consider adopting technological regulations.